Penerapan Metode Agile Scrum Pada Rancangan SisIAM4 - Faza Nadhira; Moh. Iwan Wahyuddin; Ratih Titi Komala Sari (STMIK Budi Darma, 2022)
Development of web based information systems is grown very rapidly, one of which can help the process of processing information and data, to improve performance in various fields, including in the academic. This research aims to design a web-based academic information system in schools to make it easier for Muhammadiyah 4 High School to manage student values, as well as improve students in seeing grades and schedules online. In making this website using the Hypertext Preprocessor (PHP) programming language, MySQL as a database and CodeIgniter framework, and Visual Studio Code as a medium for writing coding. The method used in making this application is Agile software development with a Scrum model and application testing using the White box testing method. With the creation of this information system is expected to help schools in managing academic data.